A profile of low vision among the blind school students in Lumbini Zone of Nepal - Sharma, MK; Thapa, H; Paudyal, B; Adhikari, RK; Dhakwa, K (Nepalese Journal of Ophthalmology, 2010)
Introduction: There is an increasing awareness about the needs of students with low vision, particularly in developing countries where programs of integrated education are being developed. However, the appropriate low vision services are usually neither available, nor affordable. Objectives: To study the profile of students with low vision in Lumbini Zone of Nepal. Materials and methods: A cross-sectional study included students with low vision from 8 integrated schools. The reading performance was measured using their own text-books with optical low vision devices prescribed for near reading. The reading rates were measured on a range of print sizes. The Standard Clinical Low Vision Assessment Form and the National Low Vision Program protocol were used. SPSS software was used in data analysis. Results: Of 46 students enrolled, 23 had a mild visual impairment, 18 had severe visual impairment and 5 were blind. Spectacles were needed for 29 (63 %) students. Of the 11 students who had been wearing glasses, the visual acuity improved in 4 with a change in prescription. 91 % of the students had near vision better or equal to 1.5 M with optical low vision services for near reading. The reading rate was 24 WPM at the age of 5 years, whereas at the age of 21 years, it was 55 WPM. Conclusion: The majority of the students with low vision need optical low vision services. Accurate refraction is important in these students. The reading rate increases significantly with improved near visual acuity. Keywords: low vision aids; low vision rehabilitation; low vision treatment DOI: 10.3126/nepjoph.v2i2.3719 Nep J Oph 2010;2(2) 127-131